INOVASI KURIKULUM “MERDEKA BELAJAR” DI ERA SOCIETY 5.0 - Mira Marisa (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2021)
Policies are made on the basis of issues and considerations related to the expected goals. Technological developments will always affect human life so that they have an impact on how people think and behave in their lives.. The education sector, from time to time has developed into a polemic for individuals if a significant policy is not implemented. The data collection method from this article is carried out by using the literature study technique, in the form of reference sources from books, journals and so on. Therefore, Indonesia is currently making this breakthrough by changing the curriculum policy to be